KECENDERUNGAN WUJUD ARSITEKTUR TRADISIONAL DURI TERHADAP ARSITEKTUR TRADISIONAL BUGIS DAN TORAJA DI KABUPATEN ENREKANG - AS, Zulkarnain (Teknosains: Media Informasi Sains dan Teknologi, 2015)
The rapid advancement of information and communication technology, about cultural interction has an impact on architecture including on Duri traditional architecturein South Sulawesi. The original shape of Duri traditional architecture.The Duri traditional architecture has undergone changes hat if unchecked will reduce ormay even eliminate authenticity, uniqueness and beauty of whicth actually become its prime attractiveness. This research aimed atexplaining the tendency development of the physical and non-physical shapes of Duri traditional architecture towards Buginese and Torajanese traditional architectures. Data collection used an observation technique and indepth interview with 13 people. Samples were taken by purposive sampling technique, and analysed by architectural matrix technique and frequency tabulation. The research result echibitsthe development of the physical shapes of Duri traditional architecture which have the same strong tendency to the Buginese traditional architecture and Torajanese traditional architecture.The non-physical aspects which have the strongest impact on the development tendency of Duri traditional architecture towards Buginese and Torajanese traditional architectures aspect is the religious aspect.The cultural interaction aspect is strong influence, the geographical location aspect is weak influence, andthe historical aspect is the weakest influence.